ITEM QUALITY IN MEASURING TEACHERS’ COMPETENCY IN CLASSROOM ASSESSMENT - Rosyafinaz Mohamat; Bambang Sumintono; Harris Shah Abd Hamid (Journal of Islamic, Social, Economics and Development, 2023)
Using the analysis of the Many Facet Rasch Model (MFRM), this study aims to examine the item quality when measuring teacher competency in Classroom Assessment (CA). The instrument utilized consists of 56 items built based on three primary constructs: knowledge in CA, skills in CA, and attitude towards CA. This study used a quantitative method using a multi-rater approach and a questionnaire distributed to the raters as part of the research design. The School Improvement Specialist Coaches (SISC+), the Head of Mathematics and Science Department, the Head of Mathematics Panel, and the Mathematics Teachers are among the 262 raters who are assessed 100 ratees. This study involved 100 secondary school Mathematics teachers as ratees. The analysis showed that MFRM has several advantages, including determining item quality, reporting rating scale findings, fit statistics, and unexpected responses. MFRM may compare the difficulty level of each item on an individual basis. In addition, MFRM can detect any unexpected responses in measurements and makes it easier for researchers to communicate their findings. MFRM offers the advantage of giving comprehensive information and contributing to a better understanding of item quality through quantitative evidence. This study clearly showed that MFRM is a viable alternative model for overcoming the multi-rater analysis limitations of CTT statistical models.